DEFLECTION OF STRAIGHT AND CAMBERED BEAMS MEASURED DURING FOURTEEN HOURS PER DAY (Journal of Engineering, 2006)
Straight and camber beams in portal frames [Footings + Columns + Beams] were studied. Deflection for period of fourteen hours in a day was measured for ten days. Peak value of deflection within a day is predicted for each one of the beams under a sustained load uniformly distributed. It is suggested that the load test is to be performed during critical period, within a day, that gives peak deflection.